A project on Petrus Hispanus: edition and study of the attributed works - Meirinhos, José (2016)
Brief description of the research project Edição Crítica e Estudo das Obras Atribuídas a Petrus Hispanus - 1 / Critical Edition and Study of the Works Attributed do Petrus Hispanus - 1 (reference: FCT: PTDC/MHC-FIL/0216/2014) based at the Instituto de Filosofia da Universidade do Porto, 2016-2019.